Temporal Genetic Stability Despite Decades of Overexploitation for Large Yellow Croaker in the East China Sea - Xu, Zhe; Dou, Shuo-Zeng; Ding, Shao-Xiong; Liu, Jin-Xian (Frontiers in Marine Science, 2022)
Almost all the commercial fishery stocks have been overexploited, resulting in dramatic populations decline and phenotypic change. Understanding the genetic effects of overexploitation have important implications for the conservation and management of fishery resources. In the present study, we investigated temporal changes of genetic diversity and spatio-temporal genetic structure in the heavily exploited large yellow croaker (Larimichthys crocea) in the East China Sea, through microsatellite analysis of historical and contemporary samples. Despite the drastic population decline, we found no significant decline in measures of genetic diversity (Ar, He and FIS). The contemporary effective population sizes were still large enough and genetic drift was not strong enough to reduce the genetic diversity of large yellow croaker significantly in the East China Sea. Furthermore, no evidence of spatio-temporal genetic structure was detected. All the analysis of genetic structure indicated that the proportion of variance explained by temporal factors was small and similar with that of spatial factors. We therefore concluded that the genetic structure of the large yellow croaker in the East China Sea has been essentially stable over the time-span of 60 years. These results suggested that the drastic population declines did not change genetic composition of large yellow croaker in the East China Sea. Based on the long-term stable temporal pattern of genetic composition, we suggested that fishing restrictions and habitat restoration should be the most direct and effective management strategy for the recovery of large yellow croaker stocks.